Recent Advances in Digital System Diagnosis and Management of Healthcare - Sartipi, Kamran; Edoh, Thierry (IntechOpen, 2021)
Technologically supported healthcare management is beginning to take center stage as advances occur in many aspects of healthcare, involving big data, artificial intelligence, and improved user interfaces. This volume provides a perspective on a number of such advances, ranging from homecare with remote network support and primary homecare to telemedicine application for pediatric cardiology. A special section with chapters on Clinical Decision Support Systems (CDSS) addresses topics in improved human interfaces, intelligent support for better quality home and institutional care, effective big data visualization for decision-makers, and gathering data from multiple sources to support the battle against resistant bacteria.